The Use of Kaili Regional Language in Improving Learning Outcomes in PAI Subjects - Muhammad Rizal Masdul; Rahmawati; Feri Payuhi; Adriansyah A. Lasawali (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
This study aims to determine the useof Kaili Regional Language in Improving Learning Outcomes in PAI Subjects at SDN 26 South Banawa". The research method used by researchers is field research with a qualitative approach. This study shows that the use of the Kaili regional language as an indicator that serves as a bridge connecting the ease of the learning process and as a controlling tool for student behavior. Furthermore, the use of kaili regional language at SDN 26 Banawa Selatan is a real effort from educators to reduce the uncontrolled rate of kaili regional language use. The technique used by educators is to start by using Indonesian and explaining the material in the Kaili regional language. The use of the Kaili regional language in improving learning outcomes in PAI subjects at SDN 26 South Banawa is inseparable from the guidelines of the Syllabus and Rpp. The assessments used by educators in the use of the Kaili regional language in improving learning outcomes are formative test assessments, subsumative tests and summative tests.